Speech Delay Due to Expressive Language Disorder with Normal Hearing: A Case Report - Benny Kurnia; Karina Witari; Safarianti (Talenta Publisher, 2023)
Background: A method is required in communication to provide information to one another, including the capacity to comprehend and create communications. Language is a mental analysis of communication that includes both receptive language (understanding) and expressive language (ability to convey feelings, information, thoughts and ideas). Objective: To be able to find out how appropriate treatment should be for patients with language disorders with normal hearing examination results. Methods: PubMed, medline, other manual searches. OAE, BERA, ASSR with normal hearing results according to the case in this patient. Expressive language disorder occurs when a child is unable to articulate or explain the substance of his opinions and ideas verbally according to his age, and OAE, BERA, and ASSR have all been tested with normal findings. Results: A child aged 2 years and 8 months was diagnosed with expressive language disorder, considering that his history, physical exams, and OAE, BERA, and ASSR tests were all normal. Conclusion: This is necessary to prevent speech and language problems and to allow cognitive, social, and scholastic skills to function properly. To enhance communication and get an improved prognosis, speech treatment and child psychologist advice should be explored.